2020
DOI: 10.1142/s021849582050003x
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effects of Sustainability Orientation in the Entrepreneurial Intention Model

Abstract: Given that business opportunities for sustainable development are increasing, it is opportune to consider the moderating effects of students’ sustainability orientations on the entrepreneurial intention model. This study aims to contribute to entrepreneurial intention research by extending insights from the theory of planned behaviour (i.e. attitudes towards behaviour, subjective norms, perceived behavioural control) by considering the moderating effects of sustainability orientation. To date, no known studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Moreover, a firm's sustainability orientation has been reported as a significant component of ethical leadership (Eisenbeiss, 2012). Notably, the significance and influences of a firm's sustainability orientation has immensely been studied in the entrepreneurship context; for instance, in entrepreneurial legitimacy (e.g., Reynolds, Sheehan, & Hilliard, 2018), entrepreneurial intention (e.g., Dickel & Eckardt, 2021;Shahidi, 2020), entrepreneurial behavior (e.g., St-Jean & Labelle, 2018), and entrepreneurial orientation (e.g., DiVito & Bohnsack, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a firm's sustainability orientation has been reported as a significant component of ethical leadership (Eisenbeiss, 2012). Notably, the significance and influences of a firm's sustainability orientation has immensely been studied in the entrepreneurship context; for instance, in entrepreneurial legitimacy (e.g., Reynolds, Sheehan, & Hilliard, 2018), entrepreneurial intention (e.g., Dickel & Eckardt, 2021;Shahidi, 2020), entrepreneurial behavior (e.g., St-Jean & Labelle, 2018), and entrepreneurial orientation (e.g., DiVito & Bohnsack, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is important here to note that someone needs to believe that entrepreneurship can improve the world, as sustainability orientation without this belief seems to hinder entrepreneurial action; however, the study mentioned-based on a student sample-did not measure the sustainability content [27]. Referring back to the findings of Shahidi [17], it becomes clear that the relationship between sustainability orientation and entrepreneurial intention remains complex and that the sustainability content of the latter and the interaction of the two need to be assessed in further detail.…”
Section: Sustainable Entrepreneurshipmentioning
confidence: 92%
“…Finally, the perceived behavioral control reflects the sensed ability of the individual to perform well in the assessed behavior and the feasibility of this. Recently, the TPB was applied to the topic of sustainable entrepreneurship by Shahidi [17], who evaluated the moderating effects of sustainability orientation on entrepreneurial intention and found that high levels of the moderator had a positive impact on the dependent variable. However, his study was not focused on measuring the sustainability content of entrepreneurial intentions and was based on a student sample.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the inclusion of environmental issues at the strategic level significantly increases the complexity of organisational change (Hart, 1995;Dangelico et al, 2017), and therefore must be supported not only by the acquisition and assimilation of new knowledge, but also by a periodic renewal of the corporate base of resources and competences. Finally, taking into account the fact that the growing awareness of environmental problems determines the decision of firms to reorient strategically towards taking activity for the benefit of the environment (Shahidi, 2020), it can be assumed that:  Proposition 1. Sensing determines the sensitivity of a firm to environmental problems, facilitating the adoption of strategic Environmental Sustainability Orientation, which leads to achieving better organisational outcomes.…”
Section: Gaining and Sustaining Competitive Advantagementioning
confidence: 99%